2023
DOI: 10.1002/anie.202216819
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Application of Supramolecular Junctions

Abstract: The convergence of supramolecular chemistry and single-molecule electronics offers a new perspective on supramolecular electronics, and provides a new avenue toward understanding and application of intermolecular charge transport at the molecular level. In this review, we will provide an overview of the advances in the characterization technique for the investigation of intermolecular charge transport, and summarize the experimental investigation of several non-covalent interactions, including π-π stacking int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 206 publications
(250 reference statements)
0
29
0
Order By: Relevance
“…As discussed above, recent research has evidently revealed the unimaginable promise of non-covalent interactions in tuning charge transport in a variety of molecules. 50,59,66 The remarkable development of supramolecular chemistry has enabled the synthesis of hundreds, if not thousands, of amazingly complex molecular structures through self-assembly as a result of the elegant mixture of covalent and non-covalent interactions. It has been well accepted that harnessing molecular self-assembly might be the most promising route to circumvent the scalability issue in future molecular-scale devices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed above, recent research has evidently revealed the unimaginable promise of non-covalent interactions in tuning charge transport in a variety of molecules. 50,59,66 The remarkable development of supramolecular chemistry has enabled the synthesis of hundreds, if not thousands, of amazingly complex molecular structures through self-assembly as a result of the elegant mixture of covalent and non-covalent interactions. It has been well accepted that harnessing molecular self-assembly might be the most promising route to circumvent the scalability issue in future molecular-scale devices.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of novel experimental designs and extreme flexibility displayed in molecular synthesis have introduced yet another unique charge transport medium -''through-space'': where charge transport is dominated by non-covalent, intermolecular delocalization of proximate p-electrons of adjacently stacked aromatic units. 66,67 p-p stacked molecules have great potential in advancing molecular electronics because they represent one unique way to simultaneously harness multiple conducting channels (through-bond and through-space) to aid molecular conductance at the single molecular level. 46,68,69 Naturally inspired, p-p stacking is also popular for providing desirable stability to biomolecules such as DNA and tertiary protein molecules.…”
Section: P-p and R-r Stackingmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular electronics is a research field that explores the use of molecules as electronic components in nanoscale devices, combining interdisciplinary research in physics, chemistry, biology, and materials science, and has made remarkable progress over the past two decades. To achieve this goal, the electrical properties of molecules at the single-molecule level have been investigated using self-assembled monolayers (SAMs) and single-molecule junctions of various small organic compounds. Recently, as an evolution of unimolecular systems, the use of π-stacked homodimers as molecular junctions has been demonstrated with a variety of π-conjugated backbones, including phenylene, thiophene, and polycyclic aromatic hydrocarbon systems . It has been reported that such π-stacked dimer junctions exhibit unique charge-transport behaviors, including quantum interference effects, , length-independent tunneling, and structural and electric responsiveness to external electric fields .…”
Section: Introductionmentioning
confidence: 99%